Recipe for Success?: Lessons for Strategic Climate Litigation from the Sharma , Neubauer , and Shell Cases - Peel, Jacqueline; Markey-Towler, Rebekkah (German law journal, 2021)
The urgency of the global climate problem has prompted an increasing turn to the courts to accelerate action. While still a relatively new phenomenon, “strategic” climate cases have been on the rise since 2015. Litigants in these cases aim to produce ambitious and systemic outcomes. However, with both time and resources limited, how might we best discern which cases have the greatest prospects of achieving cut through in the policy and public debate, and accelerating climate action? This Article contributes to developing literature evaluating the “recipe for success” in strategic climate claims. It provides a comparative analysis of three recent, high-profile wins in climate cases from Australia— Sharma —, Germany— Neubauer —, and the Netherlands— Shell —, examining their commonalities to give insight into the ingredients for successful strategic climate litigation. Our analysis shows how the three cases combine careful, strategic planning, with legal imagination and innovation to generate outcomes that heighten their capacity for broader impact. Evaluating the success of these types of prominent climate cases provides important guidance for future case design.